Gambaran Body Image Pasien Pasca Amputasi Transtibial Setelah Menggunakan Transtibial Prosthesis - Maretania Devi Maya Santi; Nur Rachmad (Jurnal Keterapian Fisik, 2018)
Abstract Background, Individual assessment of the body and its appearance is called the term body image/ self image (body image). In the act of amputation is closely related to the body image that ultimately affects the self-image of a person's appearance both psychologically and psychologically. Transfoliative amputation clients report social discomfort associated with changes in body image, negative body esteem, lack of social support and increased depression and post-traumatic stress disorder. Transtibial Prosthesis is an instrument intervention in the form of a prosthesis by being paired outside the body which aims to restore the lower limb shape and can replace the function anatomically and functionally is expected also able to increase the confidence physically and psychically to the body image (form body) of patients with transtibial amputation. Method: type is qualitative with research method that is used that is interview and observation. Result: That the increase of body image transtibial amputations after using the transtibial prosthesis. Conclusion: Based on the results of observations, interviews and analysis carried out on the use of Transtibial Prosthesis, patients now feel progress in their activities thanks to using prosthesis especially when the activity must be in public